Penggunaan Pembelajaran Cooperative Learning Permainan Bola Voli Dalam Meningkatkan Hasil Passing - Yahya, Rika; Kurniawan, Febi; Efendi, Rustam (Journal Coaching Education Sports, 2020)
This study aims to increase the used of volleyball cooperative learning to improve results in class VIII students of SMP Negeri 2 Cikarang Timur, Bekasi Regency in 2019/2020. The method of this research is a survey with a questionnaire as many as 20 students. The instrument used for data collection in this study was a questionnaire content assessment sheet. Based on the results of the study it was known that the level of used of volleyball learning cooperative learning in improving passing in VIII grade students at SMP Negeri 2 Cikarang Timur was included in the "very good" category the number of 0 students (0%), the "good" category with 12 students (0.4%), the "good enough" category with 0 students (0%), the "poor" category with 18 students (0.6 %), and the "not very good" category with a total of 0 students (0%). Meanwhile, on average, the eighth grade students of SMP Negeri 2 Cikarang Timur were included in the "less good" category, namely 18 students with a percentage (0.6%).